Configuration optimization for a plate-fin heat exchanger combining Taguchi method and multi-objective grey wolf optimizer - Zhe Xu; Changyin Zhao; Xin Ning; Mengyao Qin; Zhen Zhang; Fuquan Nie (Case Studies in Thermal Engineering)
A prediction model for the design indexes of a plate-fin heat exchanger (PFHX) is developed using the ε-NTU method and subsequently validated through experimental means. The mean discrepancy between the calculated and observed values for heat exchange was 4.27 %. The impact of the variables including hot stream flow length, cold stream flow length, triangular fin pitch, rectangular fin pitch, hot plate spacing, and cold plate spacing on the heat exchange capacity and weight of the PFHX was examined. The comprehensive evaluation method of Taguchi method indicates that triangular fin pitch has the highest contribution to FQ-G (FQ-G represents the combined parameters of heat transfer capacity and weight), while the hot stream flow length has the lowest contribution to FQ-G. In order to maximize the heat exchange capacity and minimize the weight of the PFHX, a combination optimization method of Taguchi method and Multi-objective Grey Wolf Optimizer (MOGWO) was proposed. The most sensitive parameters evaluated by Taguchi method, including triangular fin pitch, cold plate spacing, hot plate spacing and cold stream flow length, were optimized using the MOGWO. The combination optimization method of Taguchi method and MOGWO can enhance product quality while improving the optimization efficiency. The selected solutions demonstrate an increase in heat transfer capacity of 21.49 % and a reduction in weight of 3.29 % in comparison to the original structure. It indicates that the configuration optimization method is valid and can provide significant guidance for heat exchanger design.